Growing up Gronk : a family's story of raising champions - Gronkowski family. (Houghton Mifflin Harcourt, 2013)
"The Gronkowski family is a legitimate miracle. 5 towering brothers: Three who play in the NFL - a Denver Bronco, a Cleveland Brown and a record-breaking tight end with the New England Patriots, Rob Gronkowski, who is realizing a meteoric rise to a spot in NFL history. Another who played major league baseball. And the youngest, an up-and-coming Division 1 football player. Growing Up Gronk takes readers behind the scenes to tell the Gronkowski's incredible story, revealing how they were raised, how they were motivated, how they trained, how they played, even how their mother kept them fed. It all started with their father, Gordy, under whose tutelage this collection of giants has broken every rule about how 21st century athletic success functions. Beyond their monstrous size, physicality, and raw talent, Papa Gronk recognized early on that a clear commitment to fitness, health, and determination would give his boys a leg up in a way other families simply couldn't match. This unique story of the NFL's new first family reveals the secrets to the Gronkowski's collective success and opens the door a one-of-a-kind household, a veritable incubator of athletic greatness"--